Application of infrared thermal imaging technique in in-situ temperature field measurement of hydrate-bearing sediment under thermal stimulation. (15th February 2023) - Li, Xingxun; Wei, Rucheng; Li, Qingping; Pang, Weixin; Chen, Guangjin; Sun, Changyu
Abstract: Natural gas hydrate is a green energy with great development prospects. The exploitation of natural gas hydrate has been attracting much attention. The temperature field distribution of hydrate-bearing sediment is a crucial indication on the heat or mass transfer characteristics and thermal properties of hydrate-bearing sediment during hydrate exploitation. However, to date, the acquisition means of temperatures of hydrate-bearing sediment have been limited to the discrete temperature measurement by using the contact-type temperature sensors inserted into hydrate sediment. The continuous evolution of temperature field of hydrate-bearing sediment can be hardly achieved. Thus, in this study, a new method applying the non-contact and non-destructive infrared thermal imager was developed and applied in the in-situ measurement of the continuous evolution of temperature field of hydrate-bearing sediment. The results confirm the feasibility of application of the infrared thermal imaging technique in the hydrate-related research. The complete continuous temperature fields of hydrate-bearing sediment and non-hydrate-bearing sediment under thermal stimulation were imaged and compared. The results indicate that the temperature field distribution of hydrate sediment is predominately controlled by the effective thermal conductivity of hydrate-bearing sediment. In addition, the effects of the type of hydrate-bearing sediment, heating power and particle size of sediment were investigated. Highlights: A new infrared thermal imaging platform was established in the hydrate-related study. Infrared thermal image of temperature field of hydrate-bearing sediment was obtained. Continuous temperature field of sediment by thermal stimulation was in-situ measured. Effects of heating power, particle size and type of hydrate sediment were studied.